Critical synthesis of available data in Malassezia folliculitis and a systematic review of treatments. (30th April 2020) - Vlachos, C.; Henning, M.A.S.; Gaitanis, G.; Faergemann, J.; Saunte, D.M.
Abstract: Folliculitis is an inflammatory process involving the hair follicle, frequently attributed to infectious causes. Malassezia, an established symbiotic yeast that can evolve to a skin pathogen with opportunistic attributes, is a common source of folliculitis, especially when intrinsic (e.g. immunosuppression) or extrinsic (high ambient temperature and humidity, clothing) impact on the hair follicle and the overlying skin microenvironment. Our aim was to critically review the pathophysiology and clinical characteristics of Malassezia folliculitis, to describe laboratory methods that facilitate diagnosis and to systematically review treatment options. Malassezia folliculitis manifests as a pruritic, follicular papulopustular eruption distributed on the upper trunk. It commonly affects young to middle‐aged adults and immunosuppressed individuals. Inclusion into the differential diagnosis of folliculitis is regularly oversighted, and the prerequisite‐targeted diagnostic procedures are not always performed. Sampling by tape stripping or comedo extractor and microscopic examination of the sample usually identifies the monopolar budding yeast cells of Malassezia without the presence of hyphae. However, confirmation of the diagnosis with anatomical association with the hair follicle is performed by biopsy. For systematic review of therapies, PubMed was searched using the search string "(malassezia" [MeSH Terms] OR "malassezia" [All Fields] OR pityrosporum [All Fields]) AND "folliculitis" [MeSH Terms] and EMBASE was searched using the search string: 'malassezia folliculitis.mp OR pityrosporum folliculitis.mp'. In total, 28 full‐length studies were assessed for eligibility and 21 were selected for inclusion in therapy evaluation. Conclusively Malassezia folliculitis should be considered in the assessment of truncal, follicular skin lesions. Patient's history, comorbidities and clinical presentation are usually indicative, but microscopically and histological examination is needed to confirm the diagnosis. Adequate samples obtained with comedo extractor and serial sections in the histological material are critical for proper diagnosis. Therapy should include systemic or topical measures for the control of the inflammation, as well as the prevention of recurrences.